Primary cilia act as mechanosensors during bone healing around an implant - Leucht, P. (2012)
The primary cilium is an organelle that senses cues in a cell’s local environment. Some of these cues constitute molecular signals; here, we investigate the extent to which primary cilia can also sense mechanical stimuli. We used a conditional approach to delete Kif3a in pre-osteoblasts and then employed a motion device that generated a spatial distribution of strain around an intra-osseous implant positioned in the mouse tibia. We correlated interfacial strain fields with cell behaviors ranging from proliferation through all stages of osteogenic differentiation. We found that peri-implant cells in the Col1Cre;Kif3a(fl/fl) mice were unable to proliferate in response to a mechanical stimulus, failed to deposit and then orient collagen fibers to the strain fields caused by implant displacement, and failed to differentiate into bone-forming osteoblasts. Collectively, these data demonstrate that the lack of a functioning primary cilium blunts the normal response of a cell to a defined mechanical stimulus. The ability to manipulate the genetic background of peri-implant cells within the context of a whole, living tissue provides a rare opportunity to explore mechanotransduction from a multi-scale perspective.